Diverse histories of American sociology - Blasi, Anthony J. (Brill, 2005)
Annotation The collection tells the story of early American sociology from the vantage point of women, racial, ethnic, regional, and religious minorities, outsiders, and important representatives of intellectual movements that were not merged into the mainstream of the discipline.